2016
DOI: 10.1089/pho.2015.4080
|View full text |Cite
|
Sign up to set email alerts
|

Oral Decontamination of Orthodontic Patients Using Photodynamic Therapy Mediated by Blue-Light Irradiation and Curcumin Associated with Sodium Dodecyl Sulfate

Abstract: These results indicate that when associated with the surfactant SDS, the aPDT can be used as an adjutant and a convenient agent to promote the oral decontamination in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…A clinical study using the combination of aBL (450 ± 10nm) with curcumin for oral decontamination in orthodontic patients was carried out by Panhoca et al (Panhoca et al, 2016). The result showed that aBL irradiated curcumin significantly reduced the S. mutans survival rate (from 6.33 ± 0.92 to 5.78 ± 0.96 log 10 CFU, P < 0.05).…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…A clinical study using the combination of aBL (450 ± 10nm) with curcumin for oral decontamination in orthodontic patients was carried out by Panhoca et al (Panhoca et al, 2016). The result showed that aBL irradiated curcumin significantly reduced the S. mutans survival rate (from 6.33 ± 0.92 to 5.78 ± 0.96 log 10 CFU, P < 0.05).…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…Periodontal diseases have also been treated successfully by aPDI mediated by conventional PS [215217]. However, de Freitas et al [218] investigated the effect of aPDI using MB-loaded poly(lactic-co-glycolic) (PLGA) NPs (MB-NP) in a clinical pilot study with 10 adult human subjects with chronic periodontitis.…”
Section: Apdi For Treating Localized Infectionsmentioning
confidence: 99%
“…Only two recent reports have studied some of the effects of PDT as oral preventive treatment in patients undergoing orthodontic treatment . These studies concluded that PDT reduces gingival index (GI) scores and Streptococcus mutans load in saliva , which could benefit orthodontically treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Only two recent reports have studied some of the effects of PDT as oral preventive treatment in patients undergoing orthodontic treatment . These studies concluded that PDT reduces gingival index (GI) scores and Streptococcus mutans load in saliva , which could benefit orthodontically treated patients. It is important therefore to study whether the use of PDT therapy as periodontal maintenance during orthodontic treatment can improve the clinical periodontal parameters by reducing total periodontopathogenic bacteria and so modulate the host immune response and cytokine secretion profile.…”
Section: Introductionmentioning
confidence: 99%